AB0062 Ex vivo back-translation of fostamatinib's effect on joint ecm turnover shows significant effect on bone but no effect on the synovium. (15th June 2017) - Kjelgaard-Petersen, CF; Christensen, TG; Hägglund, P; Karsdal, MA; Thudium, CS; Bay-Jensen, A-C
Abstract : Background: It is important to establish translational methods that aid in pre-clinical go/no-go decision points to increase the success rate of approved DMARDs. The Spleen tyrosine kinase (Syk) inhibitor Fostamatinib (Fosta) was terminated for development for RA, due to insufficient effect on joint structure in phase III. Objectives: The objective was to use a translational system of ex vivo cultures to back-translate the insufficient effect on joint structure described in clinical studies. Methods: Human mature osteoclasts (HOC) seeded on bone, bovine cartilage explants (BEX) and human synovial explants (SME) were treated with R406 (API of Fosta) at 5μM-0.05μM. Osteoclasts were co-stimulated with 25 ng/ml M-CSF and RANKL, while BEX and SME were co-stimulated with TNFα 2 ng/mL and OSM 10 ng/mL (O+T) or TNFα 10 ng/mL, respectively. CTX-1 and Ca 2+ were measured in conditioned medium (CM) from HOC. Metabolic activity of HOC was assessed with Alamar Blue. C2M and AGNx1 were measured in CM from BEX, while acMMP3, C1M, and C3M were measured in CM from SME. The biomarkers in BEX and SME CM were measured at 4 time points and the total release were quantified by area under the curve (AUC). CTX-1, C2M, AGNx1, acMMP3, C1M, C2M and C3M were measured with ELISA. Ca 2+ was measured with ADVIA Chemistry system. Statistical differences of metabolic activity was calculated with One-way ANOVA with Dunnett's multiple comparison test. Statistical differences between biomarkers levels or AUC were calculated with Kruskall Wallis test with Dunn's multiple comparision test. Results: R406 decreased the release of CTX-1 (Fig 1 A) and Ca 2+ in a dose-dependent manner, with a significant decrease at 1μM ( P <0.01). This might be due to a toxic effect of R406 on HOC (Fig 1 B) ( P <0.05). R406 decreased the total release of C2M and AGNx1 in a dose-dependent manner in BEX. C2M was inhibited a concentrations down to 1.25μM ( P =0.034), and AGNx1 down to 5μM ( P =0.012). In SME R406 only decreased the release of C1M and C3M (Fig 1 e) significantly at 5 μM (C1M: P =0.03, C3M: P =0.046), and tended to decrease release of acMMP3 (Fig 1 f) at 5μM. The later was however not significant. Conclusions: Serum-based biomarkers of the joint ECM turnover were measured in CM from HOC, cartilage and synovial explant cultures. R406 decreased bone resorption and HOC metabolic activity in a dose-dependent manner, together with the MMP-mediated degradation of type II (C2M) collagen and aggrecanse degradation of aggrecan (AGNx1) in cartilage. However, R406 had limited effect on the inflammation driven MMP-mediated degradation of type I (C1M) and III (C3M) collagen and activation of MMP-3. CTX-1, C2M, and C3M have previously been measured in OSKIRA-1, with a profile identical to the ex vivo measurements here [1]. References: Platt A, Bay-Jensen AC, Braddock M, et al. The Effect of Fostamatinib with Methotrexate on Circulating Biomarkers of Synovium, Cartilage and Bone Metabolism: Potential Utility for Clinical Development Decision Making in Rheumatoid Arthriti [abstract]. Arthritis Rheumatol. 2016; 68 (suppl 10). Disclosure of Interest: C. Kjelgaard-Petersen: None declared, T. Christensen: None declared, P. Hägglund: None declared, M. Karsdal Shareholder of: Nordic Bioscience A/S, Employee of: Nordic Bioscience A/S, C. Thudium Employee of: Nordic Bioscience A/S, A.-C. Bay-Jensen Shareholder of: Nordic Bioscience A/S, Employee of: Nordic Bioscience A/S